A Specialized Microvascular Domain in the Mouse Neural Stem Cell Niche - Culver, James C. (Public Library of Science, 2013)
The microenvironment of the subependymal zone (SEZ) neural stem cell niche is necessary for regulating adult neurogenesis. In particular, signaling from the microvasculature is essential for adult neural stem cell maintenance, but microvascular structure and blood flow dynamics in the SEZ are not well understood. In this work, we show that the mouse SEZ constitutes a specialized microvascular domain defined by unique vessel architecture and reduced rates of blood flow. Additionally, we demonstrate that hypoxic conditions are detectable in the ependymal layer that lines the ventricle, and in a subpopulation of neurons throughout the SEZ and striatum. Together, these data highlight previously unidentified features of the SEZ neural stem cell niche, and further demonstrate the extent of microvascular specialization in the SEZ microenvironment.